Hydrochemistry on a waste disposal area of sand mining activities at Analandia, Sao Paulo State, Brazil, and their implications on the mobilization of uranium - Bonotto, Daniel Marcos [UNESP] (1998)
Groundwaters and surface waters from an area of treatment of sand for industrial purposes at Analandia municipality, nearly in the center of Sao Paulo State, Brazil, were chemically and isotopically analyzed with two aims: to evaluate if the anthropogenic activities that has taken place for the last 6 years is affecting the quality of the hydrological resources and to relate the hydrogeochemical behaviour of the uranium isotopes 234U and 238U with the pattern of circulation of groundwaters.